Characterizing Interprofessional Collaboration and Referral to Mindfulness-Based Stress Reduction Programs - Dhanesh D. Binda BS; Janice M. Weinberg ScD; Tra Nguyen MPH, MSc; Natalia E. Morone MD, MS (SAGE Publishing, 2022)
Background In 2017, the American College of Physicians (ACP) designated Mindfulness-Based Stress Reduction (MBSR), an eight-week group program, as first-line non-pharmacological treatment for chronic low back pain. However, interprofessional collaboration between mindfulness instructors and Primary Care Providers (PCP) remains largely unknown. Objective We developed a survey to assess communication between mindfulness instructors and PCPs, identify predictors of referral to MBSR, and determine areas where interventions could increase patient access to MBSR. Methods The 25-question survey was sent via email to PCPs at the Division of General Internal Medicine, University of Pittsburgh, PA, the Piedmont Health Services Family Medicine Section, Chapel Hill, NC, the Boston Medical Center General Internal Medicine and Family Medicine Sections, Boston, MA, and the UMass Memorial Medical Center Family Medicine Section, Worcester, MA. We used descriptive statistics and logistic regression to analyze the data. Results Among 118 eligible respondents, 85 (72.0%) were female PCPs, mean age was approximately 41.5±10.1, and the majority (65.2%) had been in medical practice ≤10 years. Of these PCPs, 83 (70.1%) reported familiarity with MBSR (95% CI: 62.1, 78.5), and 49 (59.0%) of them referred patients at least yearly. Of those who referred, 8 (16.3%) reported collaboration with mindfulness instructors. PCPs who were quite a bit or very much familiar with MBSR had 5.10 (1.10, 22.50) times the odds (P=.03), and those who were 50 years or younger had 3.30 times the odds (P=.04) of referring patients to MBSR. Frequency of PCPs' personal practice of mindfulness was not significantly associated with referrals (P=.30). Conclusion This is the first study to assess interprofessional collaboration between mindfulness instructors and PCPs. Suggestions for a potential integrative health care model are included; further studies on methods to augment communication and education are warranted to improve the referral process and ultimately increase accessibility and utilization of mindfulness-based programs.